Water-Tolerant Trifloaluminate Ionic Liquids: New and Unique Lewis Acidic Catalysts for the Synthesis of Chromane - Latos, Piotr; Culkin, Alice; Barteczko, Natalia; Boncel, Sławomir; Jurczyk, Sebastian; Brown, Lucy C.; Nockemann, Peter; Chrobok, Anna; Swadźba-Kwaśny, Małgorzata (Frontiers in Chemistry, 2018)
The first example of triflometallate ionic liquids, named in analogy to chlorometallate ionic liquids, is reported. Trifloaluminate ionic liquids, synthesised from 1-alkyl-3-methylimidazolium triflates and aluminium triflate, were characterised by multinuclear NMR spectroscopy and FT-IR spectroscopy, revealing the existence of oligonuclear, multiply-charged trifloaluminate anions, with multiple bridging triflate modes. Acceptor numbers were determined to quantify their Lewis acidity, rendering trifloaluminate ionic liquids as medium-strength Lewis acids (AN = ca. 65). Used as acidic catalysts in the cycloaddition of 2,4-dimethylphenol and isoprene (molar ratio 2:1) to prepare chromane, trifloaluminate systems outperformed literature systems, showing high activity (conversions 94-99%, selectivities 80-89%) and at low loadings (0.2 mol%) at 35 °C. Using these new systems as supported ionic liquid phase (SILP) on multi-walled carbon nanotubes (ionic liquid loading 16 wt%) delivered a recyclable catalytic system, with activity enhanced with respect to the homogenous regime.